Clinical Profile of Patients with Myasthenia Gravis in a Tertiary Center of Nepal - Ojha, Rajeev; Oli, Krishna K; Gajurel, Bikram P; Karn, Ragesh; Rajbhandari, Reema; Kharel, Ghanshyam (Nepal Journal of Neuroscience, 2017)
Myasthenia gravis (MG) has a cosmopolitan distribution and can affect people of all age group. Sometimes atypical presentation causes difficulty in the early diagnosis and management. Our aim is to study the clinical subtypes and manifestations of MG along with serological and electrophysiological diagnostic methods. Patients who were admitted in Neurology department or presented in Neurology outpatient department of Tribhuvan University Teaching Hospital from 2015 March to 2016 November were retrospectively reviewed. Out of 28 patients reviewed, 23 patients were included in the study. Their mean age of onset was 40.4±19.2 years; range=12 – 78 years, and 12 of them were female (52.2%). Eight patients (34.8%) were diagnosed with ocular myasthenia and 15 were patients (65.2%) of General Myasthenia. Seventeen patients (73.9%) were acetylcholine receptor (AChR) antibodies positive, one female patient was found to be muscle specific kinase (MuSK) positive. Decremental pattern in Repetitive Nerve stimulation (RNS) was reported in 11 patients (47.8%) and ice pack test was positive in 16 patients (69.3%). Ophthalmological findings are the most common presentation of MG patients. Icepack test is an easy clinical diagnostic tool for outpatient department which has both high sensitivity and specificity. RNS and antibody tests are the supporting tests useful for confirming the diagnosis. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 14-17